Principio de celeridad en los trámites de adopción: causas y consecuencias - Puga Vera, Mayerlie Nicole (2025)
The thesis project “Principle of Speed in adoption procedures: causes and consequences” demonstrates the problem of delays in the procedures prior to adoption in Ecuador, directly influencing children and adolescents waiting for a stable family. Despite the existence of a legislative framework that favors the well-being of children and adolescents, the procedures in practice normally last for many years, due to bureaucratic obstacles, lack of specialized personnel and prolonged judicial processes. This affects the rights of children to grow up in a safe family environment, causing an emotional impact on both adoptive families and the adopted. From this point of view, specific objectives emerged that were the basis for analyzing the administrative and legal barriers that hinder adoption, as well as for distinguishing the consequences of procedural delays in the lives of children and adolescents. For this reason, a mixed qualitative-quantitative approach was used for the development of the research. Exploratory research is carried out to help us study the problem that is not found in a defined way, so a better exploration is carried out, but without defined results. Several techniques are used, such as interviews with two lawyers specialized in the subject, a judge of Family, Women, Childhood and Adolescence and a master’s in clinical psychology with a mention in Child and Adolescent Psychotherapy. The survey was carried out on 31 lawyers who are not specialists in Family, Childhood and Adolescence matters, using instruments such as questionnaires. The answers showed that the slowness in the declaration of adoptability, the lack of clear information, the scarcity of resources and trained personnel in the institutions in charge of the processes, are determining variables in their delay in the procedures of the adoption processes.